Corrosion and nanomechanical behavior of high strength low alloy steels 1. Issue 7 (29th December 2017) - Ghosh, Rahul; Venugopal, Arjunan; Karthikeyan, Muniyandi K.; Narayanan, P. Ramesh; Pant, Bhanu; Cherian, Roy M.
Abstract : The effect of electro‐slag refining (ESR) processing with niobium inoculation and increased carbon content of high strength low alloy steel was examined using electrochemical corrosion and nanomechanical test methods. The results indicate that ESR processing with niobium inoculation effectively improves the corrosion resistance of the steel by lowering the corrosion rate. This was shown due to refinement in grain size along with freedom from inclusions. Post test observation after potentiodynamic test revealed pitting corrosion attack of the steel processed through conventional melting process and its absence in case of ESR (with niobium inoculation) processed steel. Higher carbon content of 0.29 wt% effectively enhances the strength and hardness of the modified steel for use in larger rocket boosters. The lower Lc2 and lower friction coefficient (SFC) values obtained for the ESR processed (with niobium inoculation) steel during scratch test demonstrated that the hardness and wear resistance is better when compared to the conventional steel. Abstract : The effect of electro‐slag refining (ESR) processing with niobium inoculation and increased carbon content of high strength low alloy steel was examined using electrochemical corrosion and nanomechanical test methods. The results indicate that ESR processing with niobium inoculation effectively improves the corrosion resistance of the steel by lowering the corrosion rate.